Обґрунтування інноваційних та інвестиційних проектів підприємства за умов ризику - Ларка, Людмила Сергіївна (НТУ "ХПІ", 2017)
Визначено вплив кон’юнктури ринку на ступінь підприємницьких ризиків підприємства. Метою статті є аналіз стратегії інвестування підприємства в умовах ризику. Проаналізовано інвестиційний клімат України, який впливає на інноваційну та інвестиційну активність підприємств. Висвітлено взаємозв’язок між інноваційно-інвестиційною діяльністю підприємства та ефективністю управління його потенціалом. Наведено особливості ціноутворення на інноваційну продукцію за умов ризику. Визначено особливості оцінювання систем и цілей портфелю інноваційних проектів. Показана необхідність визначення соціально-економічного ефекту проектів при обґрунтуванні напрямів удосконалення інноваційної діяльності в умовах ризику.

The influence of market conditions on the degree of entrepreneurial risks of the enterprise is determined. The purpose of the art icle is to analyze the strategy of investing in a risk environment. The investment climate in Ukraine is analyzed, which affects th e innovative and investment activity of enterprises. The relationship between the innovation and investment activity of the enterprise and the effectiveness of manag ing its potential are shown. Features of pricing for innovative products under risk conditions are given. The specifics of the evaluation of the system of goals of the portfolio of innovative projects are determined. The necessity of determining the socio-economic effect in justifying the directions for improving innovative activity under risk conditions is shown. The innovation and investment activity of the enterprise as components of its competitiveness are determined. It is suggested to use payment matrices as a basis for applying a certain investment strategy. The role of innovations in the economic growth of the enterprise is shown. It is suggested to use the indicator of social and economic efficiency of the project as a n indicator of the social responsibility of the enterprise.
Justification of innovation and investment projects of the enterprise in a risk environment
Keywords: SMART-оцінювання; інновації; інвестиції; стратегія інвестування; конкурентні переваги; risk; SMART-evaluation; innovation; investment; investment strategy; competitive advantages